Influence of the time passed after burning/cutting/transportation on the agrotechnological characteristics of sugar cane - da Silva, Fabio Cesar; Cezar, Marcos Antônio Azevedo; Parazzi, Clovis; da Silva, Edair Ribeiro; Tanaka, Edson Massao; Ardilles, Eduardo Humberto (Pesquisa Agropecuaria Brasileira, 1994)
The objective is to compare the effect of the time passed after burning/cutting/ transportation on the characteristics agrotechnological of the raw material aiming at sugar manufacturing. To reach this objective, two tests were made in Usina Nova América S/A, in Assis, SP. It was certified that the present SPCTS did not have enough sensibility to detect such processes as post crop, moisture and others. The weight loss with the permanence of the cane in the field was not compensated by the sugar concentration because of stem transpiration. The sugar amount per area is smaller, and decreases each hour, becoming worse after 48 hours. The parameters of raw material that explain better the influence of time on burning/cutting/transportation are pol, productivity (TC/ha) moisture, recoverable sugar ton/ha, reducing sugar, purity. Low correlation values were obtained with, the ATR, fibre and the dextrana % cane. The present system of sugar cane payment and the recoverable theoretical sugar (RTS) weren't efficient to evaluate the sugar cane quality in decomposition process, mainly in SP 70-1143, through the time passed after burning/cutting/transportation